Pengaruh Audit Fee Stickiness Terhadap Kualitas Audit - Jannah, Ayudia Putri Aliffia; Harymawan, Iman (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2021)
This study aims to obtain empirical evidence regarding the association between Audit Fee Stickiness (which is divided into Upward and Downward stickiness) with Audit Quality. Audit fee stickiness is measured by capturing the percentage change in actual audit fees in reaction to a 1% increase or decrease in expected audit fees. Whereas audit quality is measured by discretionary accruals using the model of Modified Jones. 652 samples were selected from listed companies on the Indonesia Stock Exchange during 2014 – 2018. The research finding shows that audit fees are less sticky upward in Indonesia. Whereas less sticky upward of audit fees positively associated with audit quality and less sticky downward of audit fees were negatively associated with audit quality. Penelitian ini bertujuan untuk mendapatkan bukti empiris mengenai pengaruh kekakuan harga audit (Audit Fee Stickiness), yaitu Upward dan Downward stickiness terhadap Kualitas Audit. Audit fee stickiness diukur dengan perubahan prosentase actual audit fees sebagai reaksi terhadap kenaikan atau penurunan minimal 1% dari expected audit fees. Sedangkan untuk Kualitas Audit diukur menggunakan discretionary accruals model Modified Jones. Sebanyak 652 sampel dipilih dari perusahaan yang terdaftar di BEI selama tahun 2014 – 2018. Hasil penelitian menunjukkan bahwa audit fee di Indonesia cenderung untuk bersifat less sticky upward. Dengan hasil temuan yaitu terdapat pengaruh positif terhadap kualitas audit apabila kekakuan harga audit bersifat less sticky upward. Serta terdapat pengaruh negatif terhadap kualitas audit apabila kekakuan harga audit bersifat less sticky downward.